A Place to be Together:: Cultivating Spaces of Discomfort and Not Knowing in Visual Analysis. The Collaborative Seeing Studio. - Restler, Victoria; Luttrell, Wendy; Chapin, David (Outlines. Critical Practice Studies, 2021)
This article describes our transmethodological practice and the affective space of making and making sense of visual research in community. We purposefully embrace complexity and richness in visual data analysis, rather than seeking to reductively avoid doubt and uncertainty. To do this, we bring multiple ways of seeing together into a collaborative, poly-vocal construction. Our ‘studio’ is designed to be a safe space for risk and creativity. We are at different levels of experience and confidence, but we all learn from each other. Seeing collaboratively depends on translating our ways of reading visual material “out of our heads” and “into our shared space.” In the sense that we love what we are doing, we revel at opening ourselves to new possibilities. In-Progress: Victoria Restler Narrates a Collaborative Seeing Studio Session. Wendy Luttrell leads us into collaging as both metaphor and tools of Collaborative Seeing. We end with a brief reflection.